Safety, pharmacokinetics and pharmacodynamics of a topical SYK inhibitor in cutaneous lupus erythematosus: A double‐blind Phase Ib study. Issue 11 (17th December 2020) - Walker, Alex; Erwig, Lars; Foster, Katie; Nevin, Katherine; Wenzel, Joerg; Worm, Margitta; Williams, Nicola; Ratia, Nirav; Hoang, Bao; Schneider‐Merck, Tanja; Gisbert, Sophie; Carnarius, Heike; et al.
Abstract: The immunoregulator spleen tyrosine kinase (SYK) is upregulated in cutaneous lupus erythematosus (CLE). This double‐blind, multicentre, Phase Ib study evaluated the safety, tolerability, pharmacokinetics, pharmacodynamics and clinical efficacy of the selective SYK inhibitor GSK2646264 in active CLE lesions. Two lesions from each participant ( n = 11) were each randomized to topical application of 1% (w/w) GSK2646264 or placebo for 28 days; all participants received GSK2646264 and placebo. The primary endpoint was safety and tolerability of GSK2646264, assessed by adverse event incidence and a skin tolerability test. Secondary endpoints included change from baseline in clinical activity and mRNA expression of interferon‐related genes in skin biopsies. Levels of several immune cell markers were evaluated over time. Eight (73%) participants experienced ≥ 1 adverse event (all mild in intensity), and maximal dermal response was similar for GSK2646264 and placebo. The expression of several interferon‐related genes, including CXCL10 and OAS1, showed modest decreases from baseline after 28 days of treatment with GSK2646264 compared with placebo. Similar findings were observed for CD3 + T cell and CD11c + dendritic cell levels; however, overall clinical activity remained unchanged with GSK2646264 vs. placebo. Further studies are warranted to assess SYK inhibitors as potential treatment for CLE.